The National Teacher Examinations (NTE) Commons Revision Survey Final Report of the Results of a National Survey to Review Proposed Specifications for the Revised Commons Examinations of the NTE - Rosner, Frieda; Grandy, Jerilee; Educational Testing Service, Princeton, NJ. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1982)
In July of 1981, the Policy Council of the National Teacher Examinations (NTE), in conjunction with the Educational Testing Service in Princeton, New Jersey, completed a series of national surveys to review proposed changes in the NTE Commons Examinations. The survey was designed to tap varying perspectives on the proposed test content and its relationship to teacher education curricula and existing requirements for entry-level teaching positions of elementary and secondary school teachers. The three elements of the proposed test used in the survey were general knowledge, communication skills, and professional knowledge. The nationally sampled populations included deans of education, professional education faculty, English department heads, elementary and secondary level principals and teachers, student teachers, state and local boards of education, and school-based parent groups. A need for greater clarity in professional education and more weight on the processes than on the context of teaching were indicated. Items in the general education fields were generally acceptable, and communications skills were a high priority. Emphasis for all groups of respondents was on useful and job-related knowledge and skills needed by beginning teachers. Interpersonal skills were stressed in all areas. Responses revealed high expectations regarding teacher literacy and teacher awareness of current real life concerns. Sample questionnaires used in the survey are appended, along with tables containing the demographic and rating statistics of each response group. (JD)
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Beginning Teachers; Higher Education; Interpersonal Competence; Preservice Teacher Education; Teacher Certification; Teacher Education Curriculum; Teacher Evaluation; Teacher Qualifications; Teaching Skills; Test Items; Test Validity; Tests; National Teacher Examinations; Reports, Research; Numerical/Quantitative Data